Broadband modulation of terahertz waves through electrically driven hybrid bowtie antenna-VO2 devices. Issue 1 (December 2017) - Han, Chunrui; Parrott, Edward; Humbert, Georges; Crunteanu, Aurelian; Pickwell-MacPherson, Emma
Abstract Broadband modulation of terahertz (THz) light is experimentally realized through the electrically driven metal-insulator phase transition of vanadium dioxide (VO2 ) in hybrid metal antenna-VO2 devices. The devices consist of VO2 active layers and bowtie antenna arrays, such that the electrically driven phase transition can be realized by applying an external voltage between adjacent metal wires extended to a large area array. The modulation depth of the terahertz light can be initially enhanced by the metal wires on top of VO2 and then improved through the addition of specific bowties in between the wires. As a result, a terahertz wave with a large beam size (~10 mm) can be modulated within the measurable spectral range (0.3–2.5 THz) with a frequency independent modulation depth as high as 0.9, and the minimum amplitude transmission down to 0.06. Moreover, the electrical switch on/off phase transition depends very much on the size of the VO2 area, indicating that smaller VO2 regions lead to higher modulation speeds and lower phase transition voltages. With the capabilities in actively tuning the beam size, modulation depth, modulation bandwidth as well as the modulation speed of THz waves, our study paves the way in implementing multifunctional components for terahertz applications.